Sejarah Agama-Agama (Studi Historis Tentang Agama Kuno Masa Lampau) - Nurlidiawati Nurlidiawati (Rihlah : Jurnal Sejarah dan Kebudayaan, 2015)
This essay aims to describe the history of ancient religions development. This paper focuses on three ancient religions, i.e the belief of ancient Egypt, Zoroastrianism and Shinto. The result of this essay finds three conclusions. First, the belief of ancient Egypt started from each activities of Nile River society. Ancient Egypt society is a polytheism peoples (worshipping for many god). The supreme god is Ra as the sun god.  God devided into parts i.e greatest god and smallest god. Second, Zoroastrianism or Majusi is the religion had revealed to Zarahustra as a prophet. This religion teaches about the singleness god. Holy Scripture of Majusi is Zebdawesta. It teaches about humanity, god and the process of creation, ethics, deads, the judgement and resurrection. There were a lot of sect in Zoroastrinism such as Shensai group, Qadimi group and Fasli group. Moreover, there were lot of ideologies in it, like mana, madzdak and zindiq. Third, Shinto is the genuine religion of Japanese. The precept of Shinto contains two credences i.e worships to nature and worships to ancesto (animism). There are four scripture of Shinto i.e Kojiku, Nihongi, Yengishiki and Mayoshiu.  Further, Shinto has lot of sects such as imperial Shinto, Folk Shinto, Sect Shinto and Shrine Shinto.